Analysis of Nanodipoles in Optical Nanocircuits Fed by Gaussian Beam. (17th June 2014) - Costa, Karlo; Dmitriev, Victor; Souza, Janilson; Silvano, Gustavo
Abstract : We analyze impedance matching and excitation properties of a plasmonic optical nanocircuit composed by a receiving and an emitting dipole connected by a two-wire optical transmission line. The circuit is fed by a circular Gaussian beam focused on the receiving dipole. The numerical analysis is performed by linear method of moments with a given surface impedance of gold cylindrical conductors. With this model, we analyze the variation of standing-wave response along the circuit in function of some geometrical parameters. We present some conclusions concerning impedance matching between the transmission line and the emitting dipole and coupling between the receiving dipole and the incident Gaussian beam.